How native T1 and T2 mapping is influenced by sex and training load? Cardiac magnetic resonance imaging in young elite athletes and less active individuals. (11th May 2022) - Szabo, L; Dohy, Z; Juhasz, V; Balla, D; Kiss, A R; Gregor, Z; Szucs, A; Babity, M; Kiss, O; Csulak, E; Sydo, N; Hirschberg, K; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): This study was financed by the Ministry of Innovation and Technology NRDI Office within the framework of the Artificial Intelligence National Laboratory Program. LS is supported by the EACVI Research Grant 2021. Introduction: Cardiac adaptation due to regular and intense exercise is a well-known phenomenon. Cardiac magnetic resonance (CMR) imaging is a well suited, highly reproducible technique that has a vital role in differentiating physiological adaptation and pathological alterations. Native T1 and T2 mapping enable the quantitative assessment of tissue characteristics without the administration of contrast material. These techniques are increasingly used in studies aiming to consider subtle differences. However, the sex-and training-dependence of native T1 and T2 mapping values remains incompletely understood. Purpose: We aimed to describe the differences in native T1 and T2 mapping among healthy athletes and less active individuals. Methods: We enrolled healthy elite athletes (n=88, 56 male, 25±5 years) and healthy volunteers (n=82, 46 male, 25±3 years) to undergo CMR examinations at our Centre. Healthy elite athletes performed high sports activity levels (>10 hours/week) and competed nationally or internationally. Sex- and age-matched healthy volunteers engaged in ≤6 hours/week of sports activity. Standardized CMR protocol included short- and long-axis cine images covering the entire left (LV) and right (RV) ventricle and native T1 and T2 mapping in basal, midventricular and apical slices. Results: Athletes had consistently higher LV and RV volumes and mass indexes compared to healthy volunteers (p<.001 for all). Native T1 mapping was lower in athletes than in the control group (T1: 954±24 ms vs 970±23 ms; p <.001). T1 mapping showed a moderately strong negative correlation to markers of cardiac adaptation, including LV mass, end-diastolic volume and stroke volume indexes (p<.001 for all). Moreover, we found a negative correlation between native T1 and training hours (Rho: -0.302; p<.001). On the other hand, native T2 mapping showed no difference between athletes and less active controls. Furthermore, T2 correlated with LV shape features but not with training hours. We found that mapping values differed between sexes, both in the athletic and control groups. Females showed slightly higher values compared to their male counterparts (T2: 46±2 vs 43±2; p<.001). Finally, native T1 mapping was associated with training hours and sex in our multiple linear regression model, adjusted for age, resting heart rate, body mass index, body surface area and LVM (p<.001). While T2 mapping was associated only with sex considering the same covariates. Conclusion: Our study demonstrates the importance of sex-matched controls in CMR studies evaluating mapping parameters. Moreover, the consideration of exercise load seems paramount in the case of T1 mapping.